Halal Heritage Tourism The Governance And Innovative Models Of Halal Heritage Tourism in Asia: Integrating Adat. Sharia Guarantee, and Sustainable Experience Economy - Anggista Setia Kurniawan; Eko Riyan Dalu; M Riyansah; Mardanita Zahra; Maisyah Maisyah; Joni Hendra K (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Halal tourism in Asia has grown into a strategic sector that significantly contributes to regional economic development. As home to the world’s largest Muslim population, Asia continues to experience increasing demand for halal-friendly travel services. The development of halal tourism encompasses various aspects such as halal food certification, Muslim-friendly accommodations, prayer facilities, and Sharia-compliant tourism activities. In addition, digitalization through halal travel applications and virtual tours of Islamic heritage sites accelerates access to information and enhances traveler convenience. The integration of local culture with Islamic values strengthens destination character and provides unique, authentic travel experiences. Supporting industries such as halal culinary businesses, modest fashion, and halal travel services are also rapidly expanding, creating a broad and sustainable halal economic ecosystem. Halal destination branding across Asia is reinforced through digital campaigns, government collaboration, and standardized service provision. The concept of halal green tourism is becoming increasingly relevant as it combines environmental sustainability principles with Islamic teachings on nature preservation. International collaboration between Muslim and non-Muslim countries further expands halal travel routes and enhances cross-cultural cooperation. Overall, halal tourism in Asia not only presents economic opportunities but also serves as a medium for cultural diplomacy, local identity strengthening, and the development of an inclusive tourism industry. With proper strategies and continuous collaboration, Asia has the potential to become the future global center of halal tourism